Serum PAI-1/BDNF Ratio Is Increased in Alzheimer's Disease and Correlates with Disease Severity - Angelucci, Francesco; Veverova, Katerina; Katonová, Alžbeta; Vyhnalek, Martin; Hort, Jakub (ACS omega, 2023)
We previously demonstrated that serum levels of plasminogen activator inhibitor-1 (PAI-1), which inhibits both the tissue plasminogen activator (tPA) and plasmin activity, are increased in patients with Alzheimer's disease. tPA/plasmin not only prevents the accumulation of β-amyloid in the brain but also is involved in the synthesis of the brain-derived neurotrophic factor (BDNF), a neurotrophin whose levels are reduced in Alzheimer. In the present study, we compared BDNF serum levels in Alzheimer patients with dementia to those in Alzheimer patients with amnestic mild cognitive impairment and to cognitively healthy controls. Moreover, we examined whether the PAI-1/BDNF ratio correlates with disease severity, as measured by Mini-Mental State Examination. Our results showed that BDNF serum levels are lower (13.7% less) and PAI-1 levels are higher in Alzheimer patients with dementia than in Alzheimer patients with amnestic mild cognitive impairment patients (23% more) or controls (36% more). Furthermore, the PAI-1/BDNF ratio was significantly increased in Alzheimer patients as compared to amnestic mild cognitive impairment (36.4% more) and controls (40% more). Lastly, the PAI-1/BDNF ratio negatively correlated with the Mini-Mental score. Our results suggest that increased PAI-1 levels in Alzheimer, by impairing the production of the BDNF, are implicated in disease progression. They also indicate that the PAI-1/BDNF ratio could be used as a marker of Alzheimer. In support of this hypothesis, a strong negative correlation between the PAI-1/BDNF ratio and the Mini-Mental score was observed.